The Suffering of Migration in Abdullah Hussain's Short Stories - Hina Ali (بازیافت, 2021)
The readers of Urdu literature need not to be introduced to the name of Abdullah Hussain.The characters of his short stories are some of unforgettable ones in Urdu on the basis of their uniqueness. Though much critical work on him has been done in many aspects, we, in this essay, have analyzed various colors of exile and migration in his short stories.